Mock terrorists decisions’ concerning use of the internet for target selection: a red-team approach - Romyn, David J. (Psychology, crime & law, 2018)
In this study we sought to identify which locations appear more, or less, attractive to a terrorist in planning an attack and to investigate what attributes of those locations influence preferences. A sample of undergraduate university students (N = 147) were given the role of terrorists, and provided with five potential attack locations, including a pedestrian mall, a shopping center, a train station, a university and an airport. After using the Internet to learn about the target locations, participants placed the locations in rank-order from most to least preferred as targets and indicated why they had selected those targets. Results showed both a clear rank-order of target preferences: locations perceived as being more crowded were more preferred, while locations with a greater security presence were less preferred. Results also demonstrated a moderate positive correlation between the amount of online information viewed for a specific location and the preference for that location as a terrorist target, where participants who viewed more online content for a particular location were more likely to also prefer that location as a terrorist target. Findings from this study can potentially be used to reduce the likelihood of a terrorist attack occurring on specific locations, by altering the publicly available information on that location regarding the security and how crowded that location is.